(untitled) (Journal of the College of Basic Education, 2024)
The study aimed To investigate the danger of cultural globalization On the Islamic community , and explaining its positive and negative effects, How does it affect people’s lives, thoughts, and personal beliefs, How to preserve Islamic identity and export deviant ideas that aim to obliterate Islamic identity , And confront the attacks it faces from its enemies. Therefore, the research hypothesis is based on the impact of cultural globalization on Islamic societies , And how its repercussions and impact on the intellectual, social and economic aspects .